Lithium ion battery electrolyte based on chalcogenide cyclic compound, preparation method of lithium ion battery electrolyte and ternary lithium ion battery

By introducing a sulfide cyclic compound electrolyte with a specific structure into lithium-ion batteries, the thermal stability and cycle life issues of NCM ternary materials have been solved, thereby improving the cycle performance and lifespan of the batteries.

CN121035340APending Publication Date: 2025-11-28DONGGUAN UPC IND & TRADE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511211004.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing lithium-ion batteries, especially those using high-energy-density NCM ternary materials, suffer from poor thermal stability and cycle life.

Method used

A lithium-ion battery electrolyte based on sulfide cyclic compounds is used, including cyclic carbonates, chain carbonates and lithium salt systems with specific structures. By generating a stable battery-electrolyte interface at the electrode interface, the phase transition of NCM622 cathode material is suppressed, the battery impedance is reduced and the dissolution of metal ions is suppressed.

Benefits of technology

It significantly improves the cycle performance and battery life of ternary lithium-ion batteries, especially the cycle performance and life of NCM622 ternary lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035340A_ABST
    Figure CN121035340A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery electrolyte based on a chalcogenide cyclic compound, a preparation method of the lithium ion battery electrolyte and a ternary lithium ion battery. The lithium ion battery electrolyte comprises an organic solvent system, a lithium salt system and an additive system, the organic solvent system comprises at least one cyclic carbonate and at least one chain carbonate; the additive system comprises a chalcogenide cyclic compound, and the chalcogenide cyclic compound has the following structural formula; an X group is selected from any one of the following groups; wherein the Y group, the Y1 group and the Y2 group are respectively and independently selected from any one of halogen, alkyl, alkenyl, alkynyl, aryl, alkoxy, amino, silicon group and carboxyl; according to the invention, the cycle life of the ternary lithium ion battery can be effectively prolonged, the cycle performance of the ternary lithium ion battery (especially an NCM622 ternary lithium ion battery) can be obviously enhanced, and the service life of the ternary lithium ion battery can be obviously prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion batteries, specifically relating to a lithium-ion battery electrolyte based on sulfide cyclic compounds and its preparation method, as well as a ternary lithium-ion battery. Background Technology

[0002] Since their commercialization, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage systems. The electrolyte, as a crucial component of lithium-ion batteries, plays a vital role in ion transport and charge conduction between the positive and negative electrodes. An ideal lithium-ion battery electrolyte needs to meet requirements such as high ionic conductivity, high chemical and thermal stability, a wide electrochemical window, good compatibility with other battery components, and safety, non-toxicity, and non-polluting properties, thereby improving the stability of the positive electrode material and extending the battery's cycle life.

[0003] However, existing lithium-ion batteries generally suffer from poor thermal stability and cycle life. In particular, NCM ternary materials with high energy density urgently need to improve their defects in thermal stability and cycle life. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a lithium-ion battery electrolyte based on sulfide cyclic compounds and its preparation method, as well as a ternary lithium-ion battery, which effectively improves the cycle life of ternary lithium-ion batteries and can significantly enhance the cycle performance and battery life of ternary lithium-ion batteries (especially NCM622 ternary lithium-ion batteries).

[0005] The technical solution adopted in this invention is as follows: A lithium-ion battery electrolyte based on a chalcogenide cyclic compound includes an organic solvent system, a lithium salt system, and an additive system; the organic solvent system includes at least one cyclic carbonate and at least one chain carbonate; the additive system includes a chalcogenide cyclic compound, wherein the chalcogenide cyclic compound has the following structural formula: The X group is selected from... , , , Any one of the following; wherein the Y group, Y1 group, and Y2 group are each independently selected from any one of halogen, alkyl, alkenyl, alkynyl, aryl, alkoxy, amino, silyl, and carboxyl groups.

[0006] Preferably, the sulfide cyclic compound accounts for 0.01-3% of the electrolyte in the lithium-ion battery by mass; more preferably, it accounts for 0.1-2%.

[0007] Preferably, the cyclic carbonate accounts for 15-35% of the mass fraction of the electrolyte in the lithium-ion battery; the chain carbonate accounts for 55-75% of the mass fraction of the electrolyte in the lithium-ion battery.

[0008] Preferably, the cyclic carbonate is ethylene carbonate (EC) and / or propylene carbonate (PC); the chain carbonate is ethyl methyl carbonate (EMC) and / or dimethyl carbonate (DMC) and / or diethyl carbonate (DEC).

[0009] Preferably, the lithium salt system includes any one or a mixture of several of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalateborate)borate (LiBOB), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiOTf), and lithium tetrafluoroborate (LiBF4).

[0010] Preferably, the concentration of the lithium salt system in the electrolyte of the ternary lithium-ion battery is 0.5-2 mol·L⁻¹. -1 .

[0011] Preferably, the chalcogenide cyclic compound comprises the following structure: , , , , Any one or a mixture of several of them.

[0012] Preferably, the additive system further includes the combined use of at least two of the following: ethylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), propanesulfonate lactone (PS), and lithium difluorooxalate borate (LiODFB), which account for 0.5-5% of the mass fraction of the lithium-ion battery electrolyte.

[0013] Preferably, a method for preparing a lithium-ion battery electrolyte based on a sulfide cyclic compound as described above involves mixing raw materials of an organic solvent system to obtain an organic solvent mixture, freezing the organic solvent mixture for 1-3 hours, adding the lithium salt system to the organic solvent mixture for mixing, and finally adding an additive system for mixing to obtain the electrolyte for the lithium-ion battery.

[0014] Preferably, a ternary lithium-ion battery uses a lithium-ion battery electrolyte based on a chalcogenide cyclic compound as described above; its positive electrode active material includes lithium nickel cobalt manganese oxide (LiNiO) as a ternary positive electrode material. x Co y Mn 1-x-y O2, NCM, preferably NCM622.

[0015] The chalcogenide cyclic compound provided in this application has a unique and novel cyclic structure. When used as an additive in lithium-ion battery electrolytes, it helps to form a stable battery-electrolyte interface at the electrode interface, which can significantly suppress the phase transition of NCM622 cathode ternary material. This can effectively reduce the impedance of lithium-ion batteries, suppress the dissolution of metal ions, and thus effectively improve the cycle life of ternary lithium-ion batteries. It can significantly enhance the cycle performance and battery life of ternary lithium-ion batteries (especially NCM622 ternary lithium-ion batteries). Detailed Implementation

[0016] This embodiment proposes a chalcogenide cyclic compound with the following structural formula: The X group is selected from; , , , Any one of the following; wherein the Y group, Y1 group, and Y2 group are each independently selected from any one of halogen, alkyl, alkenyl, alkynyl, aryl, alkoxy, amino, silyl, and carboxyl groups.

[0017] In this embodiment, the halogen is any one of fluorine, chlorine, bromine, and iodine; In this embodiment, the alkyl group is a substituted or unsubstituted C1-C. 10 Alkyl; preferably, in this embodiment, the alkyl group may be selected from any one of methyl-CH3, ethyl-C2H5, n-propyl-CH2CH2CH3, isopropyl-CH(CH3)2, n-butyl-CH2CH2CH2CH3, and tert-butyl-C(CH3)3; In this embodiment, the alkenyl group is a substituted, unsubstituted, or heteroatom-containing C2-C group. 10 Alkenyl; preferably, in this embodiment, the alkenyl group may be selected from any one of vinyl-CH=CH2, propenyl-CH2CH=CH2, and butenyl-CH2CH2CH=CH2; In this embodiment, the alkynyl group is a substituted, unsubstituted, or heteroatom-containing C2-C group. 10 Alkyne group; preferably, in this embodiment, the alkynyl group may be selected from ethynyl-C≡CH or propynyl-CH2C≡CH; In this embodiment, the aryl group is an independent aryl group or a combination of aryl group with alkyl group or heteroatom; preferably, in this embodiment, the aryl group can be selected from any one of phenyl, p-tolyl, and naphthyl groups; In this embodiment, the alkoxy group is C1-C. 10 Straight-chain or branched alkoxy group; preferably, in this embodiment, the alkoxy group can be selected from any one of methoxy-OCH3, ethoxy-OC2H5, and propoxy-OCH2CH2CH3; In this embodiment, the amino group is C1-C. 10 Straight-chain or branched primary amino, secondary amino, or tertiary amino groups; preferably, in this embodiment, the amino group can be selected from any one of methylamino-NHCH3, ethylamino-NHC2H5, dimethylamino-N(CH3)2, diethylamino-N(C2H5)2, trimethylamino-N(CH3)3, and triethylamino-N(C2H5)3. Preferably, in this embodiment, the silicon group can be selected from any one of alkylsilyl, arylsilyl, alkenylsilyl, alkynylsilyl, and combinations thereof.

[0018] Preferably, in this embodiment, the carboxyl group can be selected from any one of acetate carboxyl, oxalate carboxyl, propionate carboxyl, and trifluoroacetate carboxyl.

[0019] Preferably, in this embodiment, the chalcogenide cyclic compound comprises the following structure: , , , , Any one or a mixture of several of them.

[0020] Preferably, this embodiment proposes a method for preparing the chalcogenide cyclic compound as described above, using methanedisulfonic acid or its derivative as the initial raw material, and reacting it by adding its corresponding ligand dropwise in an organic solvent environment. Preferably, in this embodiment, the reaction temperature is controlled in the range of 5-35°C, more preferably 10-20°C; after the dropwise addition is completed, the reaction is continued at the temperature for 2-10 hours to obtain the reaction product; the reaction product is then post-treated to obtain the chalcogenide cyclic compound.

[0021] Preferably, in this embodiment, the derivative of methyl disulfonic acid is selected from any one or a mixture of several of methyl disulfonic acid hydrocarbon esters, methyl disulfonic acid amides, methyl disulfonic acid acyl halides, methyl disulfonic acid silicates, and methyl disulfonic acid anhydrides.

[0022] Preferably, in this embodiment, the molar ratio of the ligand to methyl disulfonic acid or its derivative is 1-3:1, more preferably 1.5:1; and / or the amount of organic solvent added is 3-10 times the weight of methyl disulfonic acid or its derivative, more preferably 5 times.

[0023] This embodiment also proposes a method for preparing the chalcogenide cyclic compound described above. Using the first chalcogenide cyclic compound as the initial raw material, the corresponding ligand is added dropwise in an organic solvent environment to react. After the addition is completed, the reaction is continued at a constant temperature for 2-10 hours to obtain the reaction product. The reaction product is then post-treated to obtain the second chalcogenide cyclic compound.

[0024] Preferably, in this embodiment, the molar ratio of the ligand to the first chalcogenide cyclic compound is 1-3:1, more preferably 1.5:1; and / or the amount of organic solvent added is 3-10 times the weight of the first chalcogenide cyclic compound, more preferably 5 times.

[0025] Preferably, in this embodiment, the ligand is selected from any one or a mixture of several of phosphorus trifluoride and its derivatives, phosphorus oxytrifluoride and its derivatives, and boron trifluoride and its derivatives; for example, in a specific implementation, the ligand can be: phosphorus trifluoride, phosphorus oxytrifluoride, boron trifluoride, trimethylsilyl trifluoroacetate, trimethylsilyldimethylamine, etc.

[0026] Preferably, the reaction solvent includes any one or a mixture of several of the following: ether organic solvents, carbonate organic solvents, carboxylic acid ester organic solvents, chlorinated hydrocarbons, alkanes, and nitrile organic solvents.

[0027] In this embodiment, the post-processing involved in this application mainly refers to the fine separation (using known separation processes) and / or purification (using known purification processes) of the reaction products (in a mixed state) after the reaction is completed. For example, firstly, filtration is used to initially separate the solid or liquid products and remove unreacted raw materials, by-products, and other impurities; then, extraction, crystallization, and other methods are used for further purification to obtain high-purity target chalcogenide cyclic compounds. These are all conventional technical means that can be used by those skilled in the art based on the content described in this application; finally, known analytical methods such as nuclear magnetic resonance (NMR) are used to accurately characterize the purity and structure of the final product to ensure that the target product that meets the requirements is obtained.

[0028] Preferably, this embodiment also proposes an application of the chalcogenide cyclic compound described above, in which the chalcogenide cyclic compound is added to the electrolyte of a battery; or the chalcogenide cyclic compound is used as a flame retardant or catalyst or participates in drug molecule design.

[0029] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.

[0030] Based on the above-described implementation schemes, this application further proposes the following specific embodiments: First, it should be noted that the reagent raw materials used in the following specific embodiments and comparative examples of the present invention are sourced from the following: Unless otherwise specified, all raw materials are ordinary commercially available products.

[0031] The test methods used in the specific embodiments and comparative examples of this invention are as follows: Nuclear magnetic resonance (NMR) analysis was performed using a Bruker AVANCE II 400 MHz spectrometer. It should be understood that the following specific embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0032] Example 1: A certain amount of di(trimethylsilyl) methyl disulfonate was dispersed in acetonitrile (as an organic solvent), and the temperature was controlled at 15°C. A phosphorus trifluoride acetonitrile solution (phosphorus trifluoride as a ligand) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 6 hours. The molar ratio of phosphorus trifluoride to di(trimethylsilyl) methyl disulfonate was 1.5:1, and the weight ratio of acetonitrile to di(trimethylsilyl) methyl disulfonate was 5:1. After the reaction was completed, the reaction product was concentrated using a rotary evaporator to obtain a viscous substrate. Petroleum ether was then added to the viscous substrate for extraction, yielding a product-petroleum ether solution. Further rotary evaporation was used to remove the petroleum ether, yielding a chalcogenide cyclic compound with the following structural formula: ; The chalcogenide cyclic compounds synthesized above were characterized by NMR (¹H, ¹³C): 1 ¹H NMR: δ 4.13 (2H, s); 13 C NMR: δ 31.5 (1C, s).

[0033] Example 2: A certain amount of di(trimethylsilyl) methyl disulfonate was dispersed in acetonitrile (as an organic solvent), and the temperature was controlled at 20°C. A phosphorus oxyfluoride acetonitrile solution (phosphorus oxyfluoride as a ligand) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 3 hours. The molar ratio of phosphorus oxyfluoride to di(trimethylsilyl) methyl disulfonate was 1.5:1, and the weight ratio of acetonitrile to di(trimethylsilyl) methyl disulfonate was 5:1. After the reaction was completed, the reaction product was concentrated using a rotary evaporator to obtain a viscous substrate. Petroleum ether was then added to the viscous substrate for extraction, yielding a product-petroleum ether solution. Further rotary evaporation was used to remove the petroleum ether, yielding a chalcogenide cyclic compound with the following structural formula: ; The chalcogenide cyclic compounds synthesized above were characterized by NMR (¹H, ¹³C): 1 ¹H NMR: δ 4.19 (2H, s); 13 C NMR: δ 31.8 (1C, s).

[0034] Example 3: A certain amount of di(trimethylsilyl) methyl disulfonate was dispersed in acetonitrile (as an organic solvent), and the temperature was controlled at 10°C. A boron trifluoride acetonitrile solution (boron trifluoride as a ligand) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 6 hours. The molar ratio of boron trifluoride to di(trimethylsilyl) methyl disulfonate was 1.5:1, and the weight ratio of acetonitrile to di(trimethylsilyl) methyl disulfonate was 5:1. After the reaction was completed, the reaction product was concentrated using a rotary evaporator to obtain a viscous substrate. Petroleum ether was then added to the viscous substrate for extraction, yielding a product-petroleum ether solution. Further rotary evaporation was used to remove the petroleum ether, yielding a chalcogenide cyclic compound with the following structural formula: ; The chalcogenide cyclic compounds synthesized above were characterized by NMR (¹H, ¹³C): 1 ¹H NMR: δ 4.12 (2H, s); 113 C NMR: δ 31.5 (1C, s).

[0035] Example 4: A certain amount of the product obtained in Example 1 (as the first chalcogenide cyclic compound) was dispersed in acetonitrile (as an organic solvent), and the temperature was controlled at 25°C. Trimethylsilyl trifluoroacetate (as a ligand) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 6 hours. The molar ratio of trimethylsilyl trifluoroacetate to the product was 2:1, and the weight ratio of acetonitrile to the first chalcogenide cyclic compound was 5:1. After the reaction was completed, the reaction product was concentrated using a rotary evaporator to obtain a viscous substrate. Then, diethyl ether was added to the viscous substrate for extraction to obtain a product-diethyl ether solution. The diethyl ether was further removed by rotary evaporation to obtain a chalcogenide cyclic compound with the following structural formula (as the second chalcogenide cyclic compound): ; The chalcogenide cyclic compounds synthesized above were characterized by NMR (¹H, ¹³C): 1 ¹H NMR: δ 4.14 (2H, s); 13 C NMR: δ 31.5 (1C, s), 117.7 (1C, s), 160.8 (1C, s).

[0036] Example 5: A certain amount of the product obtained in Example 1 (as the first chalcogenide cyclic compound) was dispersed in acetonitrile (as an organic solvent), and the temperature was controlled at 20°C. Trimethylsilyldimethylamine (as a ligand) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 8 hours. The molar ratio of trimethylsilyldimethylamine to the product was 2:1, and the weight ratio of acetonitrile to the first chalcogenide cyclic compound was 5:1. After the reaction was completed, the reaction product was concentrated using a rotary evaporator to obtain a viscous substrate. Then, diethyl ether was added to the viscous substrate for extraction to obtain a product-diethyl ether solution. The diethyl ether was further removed by rotary evaporation to obtain a chalcogenide cyclic compound with the following structural formula (as the second chalcogenide cyclic compound): ; The chalcogenide cyclic compounds synthesized above were characterized by NMR (¹H, ¹³C): 1 H NMR: δ 2.55 (6H, s), 4.14 (2H, s).; 13 C NMR: δ 31.5 (1C, s), 117.7 (1C, s), 160.8 (1C, s).

[0037] Comparative Example 1: This Comparative Example 1 uses the following compound provided in the example of prior patent application CN119381518A: .

[0038] The purity and yield of the products from Examples 1-5 are shown in Table 1 below:

[0039] As can be seen from Table 1 above, the reaction conditions proposed in this application are mild, and the product purity and yield are high.

[0040] To further verify the application effects achieved in Embodiments 1-5 of this application, the following comparative application experiments were conducted on the products provided in Embodiments 1-5 and Comparative Example 1 respectively: The pouch cells corresponding to Examples 1-5 and Comparative Example 1 were fabricated according to the following steps: Electrolyte preparation: Prepared in a glove box under N2 atmosphere; the water content of the organic solvent system is <10 ppm; the electrolyte includes: The organic solvent system with a mass fraction of 85.5% is specifically composed of diethyl carbonate (DEC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in a mass ratio of 1:1:1 (wt%). The lithium salt system uses 1.0 mol·L⁻¹ -1 Lithium hexafluorophosphate (LiPF6); The products provided in Examples 1-5 and Comparative Example 1 were selected respectively, and the product accounted for 1.5% of the electrolyte by mass. The rest are other additives, specifically composed of vinyl sulfate DTD: fluorovinyl carbonate FEC: lithium difluorooxalate borate LiODFB = 2:1:1 (wt%). After the raw materials of the organic solvent system are mixed evenly in a fixed ratio, the mixture is frozen and cooled for 1.5-2 hours to obtain an organic solvent mixture. The lithium salt system is added and mixed evenly. Finally, the products provided in Examples 1-5 and Comparative Example 1, as well as other additives, are added and mixed evenly for later use.

[0041] Preparation of the battery positive electrode: Using methylpyrrolidone (NMP) as a solvent, 2% (w / w) of polyvinylidene fluoride (PVDF) was uniformly dispersed to obtain a mixture. Then, 2% (w / w) of carbon nanotubes (CNTs) were added and uniformly mixed. Next, 96% (w / w) of the positive electrode active material (lithium cobalt oxide, LiCoO2) was added and mixed uniformly. The mixture was then uniformly coated onto aluminum foil using a coating machine. After drying, rolling, and cutting, the positive electrode sheet was formed with an areal density ranging from 350-450 g / cm³. 2 (Double-sided); Preparation of the battery negative electrode: Using deionized water as a solvent, 1% by mass of carboxymethyl cellulose (CMC) is uniformly dispersed to obtain a mixture. Then, 2% by mass of conductive carbon black (SP) and 96% by mass of negative electrode active material (specifically, vapor-deposited silicon carbon, material type SH-SO2) are added and uniformly mixed. Finally, 1% by mass of styrene-butadiene rubber (SBR) is added and uniformly mixed. After uniform mixing, the mixture is evenly coated onto copper foil using a coating machine. After drying, rolling, and cutting, the negative electrode sheet is formed with an areal density ranging from 200-350 g / cm³. 2 (Double-sided); To further demonstrate the effectiveness of the implementation, this application also includes the following comparative examples 2-6: Comparative Example 2: The rest of the technical solutions of Comparative Example 2 are the same as those of Example 1, except that the product in Example 2 is replaced with the additive ethylene carbonate (VC).

[0042] Comparative Example 3: The rest of the technical solutions of Comparative Example 3 are the same as those of Example 2, except that the product in Example 3 is replaced with the additive ethylene carbonate (VC).

[0043] Comparative Example 4: The remaining technical solutions of Comparative Example 4 are the same as those of Example 3, except that the product in Example 4 is replaced with the additive ethylene carbonate (VC).

[0044] Comparative Example 5: The rest of the technical solutions of Comparative Example 5 are the same as those of Example 4, except that the product in Example 5 is replaced with the additive ethylene carbonate (VC).

[0045] Comparative Example 6: The rest of the technical solutions of Comparative Example 6 are the same as those of Example 5, except that the product in Example 6 is replaced with the additive ethylene carbonate (VC).

[0046] Therefore, we obtained pouch cells assembled from the electrolytes provided in Examples 1-5 and Comparative Examples 1-6, respectively, using the products provided as specific additives. The electrolyte usage of each pouch cell was 4 g / Ah. Then, the following performance comparison tests were conducted on each pouch cell: Three groups of each soft-pack battery corresponding to Examples 1-5 and Comparative Examples 1-6 were made. Each group was cycled for 300 cycles at 25°C, 45°C and 60°C respectively. The charge and discharge conditions used for each cycle test were: charge and discharge rate of 1C / 1C and voltage range of 2.5V-4.2V. The measured capacity retention rates of the lithium-ion batteries are shown in Table 2 below:

[0047] It should be noted that the chalcogenide cyclic compounds provided in this embodiment can also be used as flame retardants or catalysts or participate in drug molecule design, showing high application prospects and adding new members to the chalcogenide compound family.

[0048] To further enhance the effectiveness of the chalcogenide cyclic compounds proposed in the above embodiments of this application in lithium-ion batteries, this embodiment also proposes a chalcogenide cyclic compound lithium-ion battery electrolyte, comprising an organic solvent system, a lithium salt system, and an additive system; the organic solvent system comprises at least one cyclic carbonate and at least one chain carbonate; the additive system comprises the chalcogenide cyclic compounds described above in this embodiment.

[0049] Preferably, in this embodiment, the sulfide cyclic compound accounts for 0.01-3% of the electrolyte mass fraction of the lithium-ion battery; more preferably, it is 0.1-2%.

[0050] Preferably, in this embodiment, the cyclic carbonate accounts for 15-35% of the mass fraction of the electrolyte in the lithium-ion battery; the chain carbonate accounts for 55-75% of the mass fraction of the electrolyte in the lithium-ion battery.

[0051] Preferably, in this embodiment, the cyclic carbonate is ethylene carbonate (EC) and / or propylene carbonate (PC); the chain carbonate is ethyl methyl carbonate (EMC) and / or dimethyl carbonate (DMC) and / or diethyl carbonate (DEC).

[0052] Preferably, in this embodiment, the lithium salt system includes any one or a mixture of several of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalateborate)borate (LiBOB), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiOTf), and lithium tetrafluoroborate (LiBF4).

[0053] Preferably, in this embodiment, the concentration of the lithium salt system in the electrolyte of the ternary lithium-ion battery is 0.5-2 mol·L⁻¹. -1 .

[0054] Preferably, in this embodiment, the additive system further includes the combined use of at least two of the following: ethylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), propanesulfonate lactone (PS), and lithium difluorooxalate borate (LiODFB), which account for 0.5-5% of the mass fraction of the lithium-ion battery electrolyte.

[0055] This embodiment proposes a method for preparing a lithium-ion battery electrolyte based on a sulfide cyclic compound as described above. The method involves mixing the raw materials of an organic solvent system to obtain an organic solvent mixture, freezing the organic solvent mixture for 1-3 hours, adding a lithium salt system to the organic solvent mixture for mixing, and finally adding an additive system for mixing to obtain the lithium-ion battery electrolyte.

[0056] This embodiment also proposes a ternary lithium-ion battery, employing a lithium-ion battery electrolyte based on a chalcogenide cyclic compound as described above; its positive electrode active material includes lithium nickel cobalt manganese oxide (LiNiO2) as the ternary positive electrode material. x Co y Mn 1-x-y O2 (NCM), preferably NCM622, which means that the ratio of N (representing nickel), C (representing cobalt), and M (representing manganese) is 6:2:2, and the performance obtained is stable. NCM811 can also be used, but the effect may be unstable. Preferably, in this embodiment, the negative electrode active material of the ternary lithium-ion battery includes graphite or a known carbon-silicon composite material.

[0057] To further verify the effectiveness of the electrolyte for ternary lithium-ion batteries proposed in the above embodiments of this application, this application further provides the following embodiments and comparative examples: Example 6: An electrolyte for a ternary lithium-ion battery, comprising: The organic solvent system with a mass fraction of 85.5% is specifically composed of ethylene carbonate EC: ethyl methyl carbonate EMC: dimethyl carbonate DMC = 3:3:4 (wt%). The lithium salt system uses 1.0 mol·L⁻¹ -1 Lithium hexafluorophosphate (LiPF6); Example 1 provides a product with a mass fraction of 1.5%; The remainder consists of other additives, specifically composed of vinyl sulfate DTD: fluorovinyl carbonate FEC: lithium difluorooxalate borate LiODFB = 2:1:1 (wt%). The electrolyte is prepared in a glove box under N2 atmosphere, ensuring that the water content of the solvent system is <10ppm. During preparation, the raw materials of the organic solvent system are first mixed evenly in a fixed ratio, and then the mixture is cooled to a freezing temperature of 1.5-2 hours to obtain an organic solvent mixture. The lithium salt system is then added and mixed evenly. Finally, the product provided in Example 1 and other additives are added and mixed evenly before use.

[0058] Example 7: The remaining technical solutions of Example 7 are the same as those of Example 6, except that in Example 7, the product provided in Example 2 is used instead of the product provided in Example 1.

[0059] Example 8: The remaining technical solutions of Example 8 are the same as those of Example 6, except that in Example 8, the product provided in Example 3 is used instead of the product provided in Example 1.

[0060] Example 9: The remaining technical solutions of Example 9 are the same as those of Example 6, except that in Example 9, the product provided in Example 4 is used instead of the product provided in Example 1.

[0061] Example 10: The remaining technical solutions of Example 10 are the same as those of Example 6, except that in Example 10, the product provided in Example 5 is used instead of the product provided in Example 1.

[0062] Comparative Example 7: The remaining technical solutions of Comparative Example 7 are the same as those of Example 6, except that in Comparative Example 7, the product provided by Comparative Example 1 is used instead of the product provided by Example 1.

[0063] Comparative Example 8: The remaining technical solutions of Comparative Example 8 are the same as those of Example 6, except that in Comparative Example 8, the organic solvent system is specifically composed of propylene carbonate PC: ethylene carbonate EC = 1:1 (wt%).

[0064] Then, the pouch cells corresponding to Examples 6-10 and Comparative Examples 7-8 were fabricated according to the following steps: Preparation of the battery positive electrode: Using methylpyrrolidone (NMP) as a solvent, 2% (w / w) of polyvinylidene fluoride (PVDF) was uniformly dispersed to obtain a mixture. Then, 2% (w / w) of carbon nanotubes (CNTs) were added and uniformly mixed. Next, 96% (w / w) of the positive electrode active material (using a ternary system NCM622) was added and mixed evenly. The mixture was then uniformly coated onto aluminum foil using a coating machine. After drying, rolling, and cutting, the positive electrode sheet was formed with an areal density ranging from 350-450 g / cm³. 2 (Double-sided); Preparation of the battery negative electrode: Using deionized water as a solvent, 1% by mass of carboxymethyl cellulose (CMC) is uniformly dispersed to obtain a mixture. Then, 2% by mass of conductive carbon black (SP) and 96% by mass of negative electrode active material (specifically graphite) are added and uniformly mixed. Finally, 1% by mass of styrene-butadiene rubber (SBR) is added and uniformly mixed. After uniform mixing, the mixture is evenly coated onto copper foil using a coating machine. After drying, rolling, and cutting, the negative electrode sheet is formed with an areal density ranging from 200-350 g / cm³. 2 (Double-sided); Therefore, we obtained: NCM622|| graphite pouch batteries assembled from the electrolytes provided by Examples 6-10 and Comparative Examples 7-8 respectively as specific additives, with each pouch battery using an electrolyte amount of 4g / Ah. Example 11: The remaining technical solutions of Example 11 are the same as those of Example 6, except that the positive electrode active material in the soft pack battery of Example 11 is the ternary system NCM811; the NCM811|| graphite soft pack battery is obtained by the assembly method of Example 6.

[0065] Then, the following performance comparison tests were conducted on each pouch battery: Three groups of each soft-pack battery corresponding to Examples 6-11 and Comparative Examples 7-8 were made. Each group was cycled for 300 cycles at 25°C, 45°C and 60°C respectively. The charge and discharge conditions used for each cycle test were: charge and discharge rate of 1C / 1C and voltage range of 2.5V-4.2V. The measured capacity retention rates of lithium-ion batteries are shown in Table 3 below:

[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0067] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A lithium ion battery electrolyte based on a chalcogen-based cyclic compound, comprising an organic solvent system, a lithium salt system, and an additive system; characterized in that, The organic solvent system comprises at least one cyclic carbonate and at least one chain carbonate; the additive system comprises a sulfur-containing cyclic compound, wherein the sulfur-containing cyclic compound comprises the following structural formula: ; the X group is selected from , , , ; wherein the Y group, the Y1 group, the Y2 group are independently selected from any one of halogen, alkyl, alkenyl, alkynyl, aryl, alkoxy, amino, silyl, carboxyl.

2. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 1, characterized in that, The sulfur-containing cyclic compound accounts for 0.01-3% of the mass fraction of the electrolyte of the lithium ion battery; more preferably 0.1-2%.

3. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 1, characterized in that, The cyclic carbonate accounts for 15-35% of the mass fraction of the electrolyte of the lithium ion battery; the chain carbonate accounts for 55-75% of the mass fraction of the electrolyte of the lithium ion battery.

4. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 1, characterized in that, The cyclic carbonate adopts ethylene carbonate (EC) and / or propylene carbonate (PC); the chain carbonate adopts methyl ethyl carbonate (EMC) and / or dimethyl carbonate (DMC) and / or diethyl carbonate (DEC).

5. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 1, characterized in that, The lithium salt system comprises any one or mixture of several of lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), lithium bis-trifluoromethylsulfonylimide (LiTFSI), lithium bis-oxalato-borate (LiBOB), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiOTf) and lithium tetrafluoroborate (LiBF4).

6. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 5, characterized in that, The concentration of the lithium salt system in the electrolyte of the ternary lithium ion battery is 0.5-2 mol·L -1 .

7. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 1, characterized in that, The sulfur-containing cyclic compound comprises the following structure: , , , , any of One or several mixtures.

8. The lithium-ion battery electrolyte based on chalcogen-based cyclic compounds according to claim 1, characterized in that, The additive system further comprises at least two of the following: ethylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), propanesulfonic acid lactone (PS), lithium difluoro-oxalato-borate (LiODFB), which accounts for 0.5-5% of the mass fraction of the electrolyte of the lithium ion battery.

9. A process for the preparation of a lithium-ion battery electrolyte based on a chalcogen-based cyclic compound according to one of claims 1 to 8, characterized in that, After mixing the raw materials of the organic solvent system, an organic solvent mixed solution is obtained; after freezing the organic solvent mixed solution for 1-3 hours, the lithium salt system is added to the organic solvent mixed solution for mixing, and finally the additive system is added for mixing, to obtain the electrolyte of the lithium ion battery.

10. A ternary lithium-ion battery, characterized in that, Lithium-ion battery electrolyte based on a chalcogen-based cyclic compound according to one of claims 1 to 8; whose positive active material comprises lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, NCM), preferably NCM622, as a ternary positive electrode material.

Citation Information

Patent Citations

  • Novel semi-solid battery and preparation method thereof

    CN119381518A